Response of the soil microbial community to petroleum hydrocarbon stress shows a threshold effect: research on aged realistic contaminated fields - Jia, Wenjuan; Cheng, Lirong; Tan, Qiuyang; Liu, Yueqiao; Dou, Junfeng; Yang, Kai; Yang, Qing; Wang, Senjie; Li, Jing; Niu, Geng; Zheng, Lei; Ding, Aizhong (Frontiers in Microbiology, 2023)
Introduction Microbes play key roles in maintaining soil ecological functions. Petroleum hydrocarbon contamination is expected to affect microbial ecological characteristics and the ecological services they provide. In this study, the multifunctionalities of contaminated and uncontaminated soils in an aged petroleum hydrocarbon-contaminated field and their correlation with soil microbial characteristics were analyzed to explore the effect of petroleum hydrocarbons on soil microbes. Methods Soil physicochemical parameters were determined to calculate soil multifunctionalities. In addition, 16S high-throughput sequencing technology and bioinformation analysis were used to explore microbial characteristics. Results The results indicated that high concentrations of petroleum hydrocarbons (565–3,613 mg•kg−1, high contamination) reduced soil multifunctionality, while low concentrations of petroleum hydrocarbons (13–408 mg•kg−1, light contamination) might increase soil multifunctionality. In addition, light petroleum hydrocarbon contamination increased the richness and evenness of microbial community (p < 0.01), enhanced the microbial interactions and widened the niche breadth of keystone genus, while high petroleum hydrocarbon contamination reduced the richness of the microbial community (p < 0.05), simplified the microbial co-occurrence network, and increased the niche overlap of keystone genus. Conclusion Our study demonstrates that light petroleum hydrocarbon contamination has a certain improvement effect on soil multifunctionalities and microbial characteristics. While high contamination shows an inhibitory effect on soil multifunctionalities and microbial characteristics, which has significance for the protection and management of petroleum hydrocarbon-contaminated soil.